2013
DOI: 10.1073/pnas.1302645110
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of miR-9 in myelopoiesis and EVI1-induced leukemogenesis

Abstract: MicroRNA-9 (miR-9) is emerging as a critical regulator of organ development and neurogenesis. It is also deregulated in several types of solid tumors; however, its role in hematopoiesis and leukemogenesis is not yet known. Here we show that miR-9 is detected in hematopoietic stem cells and hematopoietic progenitor cells, and that its expression increases during hematopoietic differentiation. Ectopic expression of miR-9 strongly accelerates terminal myelopoiesis and promotes apoptosis in vitro and in vivo. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 47 publications
(65 reference statements)
3
57
0
1
Order By: Relevance
“…This study was also consistent with study performed by Senyuk et al (21) that showed that low expression of miR-9 has leukemogenic effect in ectopic viral integration -1(EV-1) mutated AML. The study showed that miR-9 binds to specific sites causing under expression of genes called FOXO1 and FOXO3 that regulate the cell cycle and in case of under expression of miR-9,these genes are up regulated causing AML through increased rate of cell cycle consequently, increasing proliferation of myeloid precursors.…”
Section: Discussionsupporting
confidence: 82%
“…This study was also consistent with study performed by Senyuk et al (21) that showed that low expression of miR-9 has leukemogenic effect in ectopic viral integration -1(EV-1) mutated AML. The study showed that miR-9 binds to specific sites causing under expression of genes called FOXO1 and FOXO3 that regulate the cell cycle and in case of under expression of miR-9,these genes are up regulated causing AML through increased rate of cell cycle consequently, increasing proliferation of myeloid precursors.…”
Section: Discussionsupporting
confidence: 82%
“…Most interestingly, miR-9 overexpression phenocopied the effect of curcumin treatment, impairing Akt activation and FOXO1 phosphorylation. A recent report shows that FOXO1 is a direct target of miR-9 in hematopoietic cells (Senyuk et al, 2013). Taken together, these data suggest that miR-9 mediates the suppression of Akt/FOXO1 axis by curcumin in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 60%
“…The pluripotent stem cells are capable of differentiation to form any of the elements of blood, but overproliferation by these cells can lead to a condition called blood cancer or leukemia (Prasanthi et al, 2010;Li et al, 2012). This case, unregulated and abnormal white blood cells division leads to production of large number of immature blood cells (blasts), leading to impairment of various body functions, resulting in different clinical manifestations often seen in leukemia patients (Jemal et al, 2008;Senyuk et al, 2012). The exact cause of most RESEARCH ARTICLE…”
Section: Introductionmentioning
confidence: 99%